2013
DOI: 10.1016/j.nmd.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the TOMM40 gene modifies the risk of developing sporadic inclusion body myositis and the age of onset of symptoms

Abstract: Polymorphism in the TOMM40 gene modifies the risk of developing sporadic inclusion body myositis and the age of onset of symptoms.Neuromuscular Disorders, 23 (12 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…Recent studies also suggest that the TOMM40 gene rs10524523 ("523") variable length poly T repeat polymorphism is associated to a certain extent with similar AD phenotypes as those reported for APOE, such as brain white matter changes [56,57] or different biomarkers [58][59][60][61]. In addition, the TOMM40 rs2075650 G allele may be a risk factor for the development of depression [62] and sporadic inclusion body myositis [63]. Different markers at the 19q13-q13.2 chromosomal region, including the rs2075650 and rs157590 (TOMM40), rs1064725 (APOC1), and rs429358 and rs7412 (APOE) SNPs also show association with primary progressive aphasia and the behavioural variant frontotemporal dementia [64].…”
Section: Introductionmentioning
confidence: 94%
“…Recent studies also suggest that the TOMM40 gene rs10524523 ("523") variable length poly T repeat polymorphism is associated to a certain extent with similar AD phenotypes as those reported for APOE, such as brain white matter changes [56,57] or different biomarkers [58][59][60][61]. In addition, the TOMM40 rs2075650 G allele may be a risk factor for the development of depression [62] and sporadic inclusion body myositis [63]. Different markers at the 19q13-q13.2 chromosomal region, including the rs2075650 and rs157590 (TOMM40), rs1064725 (APOC1), and rs429358 and rs7412 (APOE) SNPs also show association with primary progressive aphasia and the behavioural variant frontotemporal dementia [64].…”
Section: Introductionmentioning
confidence: 94%
“…The relationship of other aggregating peptides, such as a-synuclein, may affect mitochondrial dynamics and select other specific neuronal cell types characteristic of other neurodegenerative diseases [35][36][37][38][39][40]. Clearly there is value in investigating the participation of other molecules, like synuclein and TDP-43 (transactive response DNA-binding protein 43, for mitochondrial interactions in neuronal cells specifically affected in other neuropathologically defined diseases [39,40]).…”
Section: Possible Role Of Tomm40 In Mitochondria and Metabolismmentioning
confidence: 99%
“…A polyT repeat, an intronic polymorphism (rs10524523), in the TOMM40 gene together with the APOE genotypes has been shown to influence disease susceptibility of AD [108]. It has been reported that carriers of the APOE ϵ3 allele with a very long (VL) polyT repeat alleles in TOMM40 had reduced risk of sIBM compared to controls, and this was also associated with a later age at onset of symptoms [56]. The rs10524523 may modulate expression levels of TOMM40 and/or APOE to influence disease susceptibility.…”
Section: Pathogenesis Of Sibm and Its Predisposing Genetic Factorsmentioning
confidence: 99%